PayPal: AI-driven fraud-detection - Lopez-Lira, Alejandro (Henry Stewart Talks, 2024)
This case study discusses how PayPal’s used Artificial Intelligence and machine learning technologies to drive its efforts against fraud., serving as a concrete example of how AI and ML concepts are applied effectively to enhance financial security and operational efficiency.